Retrorectal prothesis implantation: in the repair of large eventrations in the midline. - Croci, Fabio; Gastambide, Carmelo; Pérez Penco, Ernesto; Rabellino, Joaquín (Cirugía del Uruguay, 1984)
The authors present a method of laparoplasty by retrorectal lmplantation in cases of large eventrations of the mld Une or in cases of clear risk of the osteocondral margln of its ends. The factors of its indications are evaluated. Pointed out are the fundamental technlcal aspects and their varlatlons. Thls procedure has been used by the authors in twenty five instances and has thus far no caused complicatlons or recldivátion.